DIGITAL GAMES AS EDUCATIONAL POTENTIAL - EXPERIENCES AND EXAMPLES (Heritage, 2022)
Digital games also provide the opportunity to gain different experiences, broaden horizons, change behavior, and often socialize and network with other people. And while the initial stigmatization and suspicion of the scientific and professional, as well as the general public, is slowly decreasing, the trend and importance of the application of digital games in learning is growing, both at the level of individuals (through informal education) and institutions (through informal or formal). The number of researches on the effects of their application is increasing, especially since the beginning of the new millennium. This paper provides an overview of the educational potential of digital games and categorizes the results of the most significant research into the effects of their application in formal, non-formal and informal education. The paper illustrates the above results by going through numerous examples of specific mainstream or educational games.
Keywords: gaming, mainstream games, serious games, learning, education, effects